Nutrition Therapy in Australia and New Zealand Intensive Care Units: An International Comparison Study. Issue 8 (27th April 2018) - Ridley, Emma J.; Peake, Sandra L.; Jarvis, Matthew; Deane, Adam M.; Lange, Kylie; Davies, Andrew R.; Chapman, Marianne; Heyland, Daren
Abstract: Background: The Augmented Versus Routine Approach to Giving Energy Trial (TARGET) is the largest blinded enteral nutrition (EN) intervention trial evaluating energy delivery to be conducted in the critically ill. To determine the external validity of TARGET results, nutrition practices in intensive care units (ICUs) in Australia and New Zealand (ANZ) are described and compared with international practices. Methods: This was a retrospective analysis of prospectively collected data for the International Nutrition Surveys, 2007–2013. Data are presented as mean (SD). Results: A total of 17, 154 patients (ANZ: n = 2776 vs international n = 14, 378) from 923 ICUs (146 and 777, respectively) were included. EN was the most common route of feeding (ANZ: 85%, n = 2365 patients vs international: 84%, n = 12, 034; P = .258), and EN concentration was also similar (<1.25 kcal/mL ANZ: 70%, n = 12, 396 vs international: 65%, n = 56, 891 administrations; P < .001). Protein delivery was substantially below the estimated prescriptions but similar between the regions (0.6 [0.4] g/kg/day vs 0.6 [0.4] g/kg/day; P = .849). Patients in ANZ received slightly more energy (1133 [572] vs 948[536] kcal/day; P < .001), possibly because more energy was prescribed (1947 [348] vs 1747 [376] kcal/day; P < .001), nutrition protocols were more commonly used (98% vs 75%; P < .001) and included recommendations for therapies such as prokinetic agents (87% vs 51%, n = 399; P < .001) and small bowel feeding (62% vs 40%; P < .001) when compared with international ICUs. Conclusions: Key elements of nutrition practice are similar in ANZ and international ICUs. These data can be used to determine the external validity and relevance of TARGET results.